2021
DOI: 10.1093/jxb/erab102
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium chrysogenum polypeptide extract protects tobacco plants from tobacco mosaic virus infection through modulation of ABA biosynthesis and callose priming

Abstract: The polypeptide extract of the dry mycelium of Penicillium chrysogenum (PDMP) can protect tobacco plants from tobacco mosaic virus (TMV), although the potential mechanism underlying PDMP-mediated TMV resistance remains unknown. In our study, we analyzed this potential mechanism via RNA sequencing (RNA-seq) and found that the ABA biosynthetic pathway and β-1,3-glucanase, a callose-degrading enzyme, might play an important role in the PDMP-induced priming of resistance to TMV. To test our hypothesis, we successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Recent RNA sequencing (RNA-seq) and fluorescence microscopy demonstrated that pretreatment with PDMP inhibited TMV movement by increasing callose deposition around plasmodesmata (Li et al, 2021b). However, PDMP-induced callose deposition was not observed in the ABA biosynthesis mutant, which could be rescued by exogenous ABA treatment (Li et al, 2021b). These results suggested that PDMP-pretreatment induced ABA biosynthesis-dependent callose priming to protect tobacco plants from TMV infection (Li et al, 2021b).…”
Section: Physiological Transcriptional and Metabolic Changes During P...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent RNA sequencing (RNA-seq) and fluorescence microscopy demonstrated that pretreatment with PDMP inhibited TMV movement by increasing callose deposition around plasmodesmata (Li et al, 2021b). However, PDMP-induced callose deposition was not observed in the ABA biosynthesis mutant, which could be rescued by exogenous ABA treatment (Li et al, 2021b). These results suggested that PDMP-pretreatment induced ABA biosynthesis-dependent callose priming to protect tobacco plants from TMV infection (Li et al, 2021b).…”
Section: Physiological Transcriptional and Metabolic Changes During P...mentioning
confidence: 99%
“…Interestingly, noctuid moth (Spodoptera littoralis) feeding could induce a systemic [Ca 2+ ] cyt elevation in Arabidopsis, but this calcium response in Arabidopsis systemic tissues was not observed upon exposure to the synthetic PAMP flg22 (Cao et al, 2017). Pretreatment with polypeptide extract from dry mycelium of Penicillium chrysogenum (PDMP) could induce disease resistance against tobacco mosaic virus (TMV) in tobacco plants (Li et al, 2021b). Recent RNA sequencing (RNA-seq) and fluorescence microscopy demonstrated that pretreatment with PDMP inhibited TMV movement by increasing callose deposition around plasmodesmata (Li et al, 2021b).…”
Section: Physiological Transcriptional and Metabolic Changes During P...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dry mycelium of P. chrysogenum (DMP) constitutes the residual by-product of industry in penicillin production and does not contain penicillin or live mycelium. DMP has been shown to induce resistance against Fusarium wilt in melon and protect cucumber and tomato plants against the root-knot nematode Meloidogyne javanica , while an aqueous extract of DMP induces resistance in several crop species under both controlled and field conditions (see Li et al [ 368 ] and references therein). DMP has been widely used in flue-cured tobacco planting in Yunnan province, China, yielding good economic and ecological benefits [ 369 ].…”
Section: Epiloguementioning
confidence: 99%
“…DMP has been widely used in flue-cured tobacco planting in Yunnan province, China, yielding good economic and ecological benefits [ 369 ]. Recently, Li et al [ 368 ] analyzed the molecular bases of the protective effect of the DMP polypeptide extract on tobacco plant against TMV infection, concluding that β-1,3-glucanase-mediated callose deposition and the ABA pathway seem to underlie the effect.…”
Section: Epiloguementioning
confidence: 99%